Impact Analysis of Non-Tariff Measures (NTM) on Indonesian Tuna Exports to Major Destination Countries - Wiwiek Rindayati; Oktavina Widya Kristriana (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Currently, international trade is hampered in both tariff and non-tariff measures. Non-Tariff Measures (NTMs) are likely applied by some major trading countries. The NTM policy mostly applies Sanitary and Phytosanitary (SPS) and Technical Barrier to Trade (TBT). Tuna commodity is one of Indonesian potential exports facing NTM barriers. Indonesia has exported its tuna to a number of major destinations including China, Japan, Thailand, United States, South Korea, Singapore, and Vietnam. This study aims to analyze the export performance and NTMs impact on the Indonesian tuna export commodity. The methods used included descriptive analysis through inventory approach (coverage ratio and frequency index) and regression analysis of gravity model panel data from the period of 2009 – 2013 with the cross sectional data of the six major destination countries. The results show that United States as a country imposing the highest NTMs and frozen tuna is the most affected commodity group by NTM effects. The gravity model estimation results show that SPS and TBT affect tuna fish exports with positive coefficients of 0.011 and 0.015 respectively.Keywords: gravity model, NTM, SPS, TBT, tuna fish